TINJAUAN DAN PESAN PAMERAN KARTUN PEMUDA ASIA 2008 - Farid Abdullah (Universitas Trisakti, 2008)
AbstractThis essay is to understand Asian youth cartoons of a such period (2008) , and very important to look the background of that period. The theme of Asian Cartoon Exhibition is